Combining the deployment of only the distal basket segment of the EMBOTRAP III and an aspiration catheter for M2 occlusions: the ONE-SEG technique - Hamada, Yuki; Matsuoka, Hideki; Sato, Shinsuke; Kawabata, Yutaro; Iwamoto, Kana; Ikeda, Mei; Sato, Takeo; Takaguchi, Go; Takashima, Hiroshi (Frontiers in Neurology, 2024)
Background Endovascular therapy (EVT) for distal medium vessel occlusions requires prioritizing effectiveness and safety. We developed a technique combining the deployment of only the distal basket segment of the EMBOTRAP III and an aspiration catheter (AC) for M2 occlusions, called the “ONE-SEG technique,” and evaluated its clinical and technical impacts. Methods This was a retrospective review of 30 consecutive patients with M2 segment middle cerebral artery occlusion treated using the ONE-SEG technique. This method involves deploying the EMBOTRAP III through a microcatheter in only one segment and guiding the AC to the M2 origin or distal M1. The rates of final-pass expanded thrombolysis in cerebral infarction (eTICI) scores of 2c/3 or 2b/2c/3, safety (symptomatic intracranial hemorrhage [sICH]), and clinical outcomes (modified Rankin Scale [mRS] score 0–2, 0–3 at 90 days, and mortality at 90 days) were evaluated. Results Of the 30 cases, 36.7% were female, and the mean age was 75.6 ± 11.0 years. The ONE-SEG technique was used for 17 cases (56.7%, median NIHSS 10 [5–15.5]) with primary M2 occlusion and 13 cases (43.3%, median NIHSS 20 [14–22.5]) with secondary M2 occlusion after proximal thrombus removal. The successful final reperfusion rate (eTICI 2b/2c/3) was 90% overall (27/30 cases). One case (3.3%) developed sICH with secondary M2 occlusion. At 3 months, mRS scores 0–2 were seen in 64.7% of patients with primary M2 occlusion (11/17 cases) and in 23.1% (3/13 cases) with secondary M2 occlusion. Conclusion EVT using the ONE-SEG technique appears to be safe and effective for M2 occlusion.